Effects of Covid-19 on the Online Information and Documentation Degree at the University of León (Spain): The Advantages of More than a Decade Teaching Blended and Online - Rodríguez López, María del Carmen; Gallego Lorenzo, Josefa; Alvite Díez, María Luisa; Barrionuevo Almuzara, Leticia; Ceballos Roa, Rafael; Diez Diez, Ángela; Fernández Suárez, Andrés; Herrero Sánchez, Patricia; Morán Suárez, María Antonia; Olea Merino, Isabel; Rodríguez Bravo, Blanca; Santos de Paz, Lourdes (Bobcatsss, 2023)
The Degree in Library Science and Documentation of the University of León started during the 1990- 1991 academic year. This first curriculum suffered from a large presence of humanistic subjects and a low rate of experimentation granted to many subjects, caused by the integration within the Faculty of Philosophy and Letters. In the first courses, there were a high number of students. Subsequently, the decrease in the number of students in our degree caused us to initiate the change to the blended and online modalities. The Librarianship and Documentation Area of the University of León (ULe) already has a long experience in blended teaching, firstly, with the Degree in Librarianship and Documentation since the 2006/2007 academic year, using the platform aul@unileon. Currently, with the Degree of Information and Documentation in the modality blended since the 2010/2011 academic year, and in distance mode, since the 2014/2015 academic year. The new technologies have been fully introduced in university education and have facilitated the teaching-learning process through the use of interactive programs from the Internet. The main objective of this communication is to know and study what kind of multimedia tools were used by the professors of the Bachelor of Information and Documentation at the University of León in the teaching-learning process and in virtual teaching before the Covid-19; and on the other hand, observe what new tools have been introduced by the University for this reason.We will study student-teacher and student-student interaction to help promote communication and participatory learning through chat, forum, email, hangout, Skype, Meet, videoconferences, etc. In order to carry out this study, two types of methodologies will be implemented: the satisfaction surveys hosted in the Quality Office of the ULe will be studied to know the degree of satisfaction shown by students and teachers; second, the study of the annual memories.